Induksi Kalus dengan 2,4-Dpada Mikropropagasi Tanaman Stroberi (Fragraria x ananassa Duch cv. Rosalinda) - I.A. PUTRI DARMAWATI; RINDANG DWIYANI; HESTIN YUSWANTI (Fakultas Pertanian Universitas Udayana, 2013)
Callus Induction with Aplication of 2,4-D in Micropropagation of Strowberry(Fragraria xananassaDuch cv. Rosalinda). Strawberryis grown and well planted in many countries and has ahigh economic value. In Bali,thecentraproduction is in Pancasari Village,Sukasada District,BulelengRegency. The limited number and quality of seedling are the problems currently faced bystrawberry farmers at Pancasari Village. Seedlings produced by conventional propagation are limitedand are not able to meet the needs of seedling available for planting area. This study offers a solution tothe problem by applyingmicropropagationtechnique through callus induction. The research aim is tofind the optimal concentration of 2,4 - D to induce callus of strowberry. Callus that forms will be usedas the material for the next growing into young plants regenerated seedlings. This experiment used acompletely randomized design with 2 factors. The first factor was theconcentrations of 2,4 - D withfive levels of treatments, i.e.0 ; 0.5, 1.0, 1.5, and 2.0 ppm and the second factor was type of explantsused, including tip , middle and base of leaf. Results showed that2,4-D concentration of 1 and 2 ppmapplied on the base of the leaf is able to induce 100 % callus at 14 days after planting. Callus formedwas greenish white. The callus will be regeneratedinto plantlets or young plants.